Visualising mathematics for little ones - Tho, Shi Yee (2017)
This project is an exploration on children’s interests towards mathematics as a subject. I used to fair badly in mathematics until I received help from a tutor who made sure I fully understood the basic concepts. Since then, mathematics became my favourite subject as I realised to master the subject, I only had to understand the concepts. Using this experience, I intend to change the attitudes of children having difficulties with mathematics by designing a tool to let them appreciate the process of finding mathematical answers.